Professional development program for enhancing didactic-digital competence in generative artificial intelligence among provincial methodologists of basic secondary education in Villa Clara - López-Morales, Javier (2026)
The Cuban educational context is marked by the technological disruption of Generative Artificial Intelligence, which poses unprecedented challenges and opportunities for educational systems worldwide. The objective of this research is as follows: To propose a Professional Development Program in Generative Artificial Intelligence for Basic Secondary methodologies in the municipality of Santa Clara, Villa Clara, Cuba, aimed at strengthening their methodological competencies for creating didactic resources within the framework of the Third Improvement of the National Education System. This research utilized information collection and processing methods, including observation, document analysis, diagnostic survey, group interview, expert judgment, analytical-synthetic, inductive-deductive, historical-logical, systemic-structural, modeling, deductive-demonstrative, among others. The sample consisted of five methodologies from the provincial team of Villa Clara. The program proved to be relevant because it effectively addressed the use of Generative Artificial Intelligence in creating didactic resources for secondary education. Before implementation, the proposal was evaluated by experts as "Highly Relevant." Its implementation positively impacts the educational quality of the territory by promoting critical appropriation of technology, aligned with the principles of the Cuban educational model and contemporary demands for digital transformation in the pedagogical sphere.